Preparing Light Weight Concrete with Reinforced Fibers - Sldozian, Rami Joseph Aghajan (Al-Nahrain Journal of Science, 2017)
This paper is study to prepare the lightweight concrete by chemical way, and this is by adding (2%) aluminum powder by the weight of cement to obtained bubbles inside the mix of concrete. Also replace fine aggregate by the hollow ceramic powder called (Cenosphere) by ratio (25%, 50%,75% and 100%) from the weight of fine aggregate. Adding glass fibers to concrete mix by ratio the (1%, 1.5% and 2%) from the weight of cement, to enhance the mechanical properties of the samples. The results show increase in compressive and tensile strength by increase the ratio of cenosphere instead fine aggregate, and the best ratio was (50%) and (2%) aluminum, and the best ratio of fiber glass was (1.5%). Generally, decrease the density of samples when increase the ratio of bubbles and the ratio of cenosphere instead the fine aggregate, the density was (0.868 gm/cm3) float on the water at ratio (100% cenosphere). Decrease the thermal conductivity by increase the ratio of aluminum bubbles and the replacement of ceramic powder (cenosphere) instead fine aggregate. Observed also increase the high of samples from (25.26 mm) normal sample to (57.51mm) for the sample contain 100% ceramic powder and 2% aluminum powder.